2013
DOI: 10.21608/jssae.2013.51935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Planting System on Soil, Water and Rice Productivity in the Northern Part of Delta in Egypt

Abstract: Water scarcity and soil salinity are the main constrains for rice production in Egypt. Rice is the greatest consumer of water among all crops. A system of growing rice on raised beds or levees and system of rice intensification (intermittent irrigation system) where water is applied only in the furrows between beds, is hypothesized to reduce water input for rice. For water saving with considerable rice grain yield under newly reclaimed saline soil, two field experiments were conducted to innovate new rice plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…[50], Mazhar et al [51], Kumar et al [52] and Zayed et al [53]. The findings are however in contrast to the findings of Wu et al [54] who argued that tillering in rice plant is determined mostly by climatic factors like light, temperature, plant density, and nutrients.…”
Section: Tillering At 8 and 12watpmentioning
confidence: 96%
“…[50], Mazhar et al [51], Kumar et al [52] and Zayed et al [53]. The findings are however in contrast to the findings of Wu et al [54] who argued that tillering in rice plant is determined mostly by climatic factors like light, temperature, plant density, and nutrients.…”
Section: Tillering At 8 and 12watpmentioning
confidence: 96%
“…Also, the result showed that SRI saved 27% water versus continuous watering in transplanting rice [8]. While, in a field experiment carried out using various sowing systems ( traditional methods (control treatment), system of rice intensification (SRI) with intermittent irrigation system, dry rice seed on dry levees and transplanted rice on levees) where, the Results showed that the different systems of rice planting and technology significantly variation in their impact on soil properties, yield and most of yield components of rice In addition, saved water and water productivity in rice crop [9]. As observed in a field study conducting two different field experiments that applied in Bangladesh which included two methods of cultivation (raised bed sowing system, compare with traditional method).…”
Section: Introductionmentioning
confidence: 99%
“…El-Sharkawy et al, (2006) confirmed that prolonging irrigation interval (12 days) under saline soil is unfavorable for rice growth and it can be observed that flooding every 3 or 6 days should be followed to prevent the soil chemical composition from degenerating and unbalance nutrients. Zayed et al, (2013) found that irrigating every 4 days had favorable effect and improving rice growth and productivity comparing to prolonging irrigation intervals under saline soil and poor water quality. Hassan et al, (2015) indicated that the 3, 7 and 10 days intervals of irrigation consumed 50%,45% and 36% as much water as, continuous flood.…”
Section: Introductionmentioning
confidence: 99%